2012
DOI: 10.1097/mat.0b013e3182578b6a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LVAD Outlet Graft Anastomosis Angle on the Aortic Valve, Wall, and Flow

Abstract: Left ventricular assist devices (LVADs), which pump blood from the left ventricle to the aorta are an important therapy option for patients with end-stage cardiovascular diseases. Recent publications show that even with optimized LVADs fatal complications can occur because of the blood deformations around the inflow cannula or through the LVAD outlet graft-aorta anastomosis. This study investigates the effects of the anastomosis geometry on the flow through the aorta, on the pressure and wall shear stress (WSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 18 publications
(15 reference statements)
1
25
0
Order By: Relevance
“…This highly heterogeneous WSS distribution coupled with a constant exposure of high WSS in a small region of the aortic arch can strongly influence endothelial cell function and arterial wall health 4345 . Other research groups have also found regions of elevated WSS at the location of LVAD graft out-flow impingement 25,29, 30,46,47 . While the more acute angles reduce the WSS maximum on the aorta and increases the values near the brachiocephalic and carotid ostia, possibly reducing the risk of endothelial dysfunction in the aortic root and the temporary lodging of microthrombi at the upper body arterial bifurcations before leaving as larger thrombus, no single configuration globally minimizes WSS on the arterial walls.…”
Section: Discussionmentioning
confidence: 83%
“…This highly heterogeneous WSS distribution coupled with a constant exposure of high WSS in a small region of the aortic arch can strongly influence endothelial cell function and arterial wall health 4345 . Other research groups have also found regions of elevated WSS at the location of LVAD graft out-flow impingement 25,29, 30,46,47 . While the more acute angles reduce the WSS maximum on the aorta and increases the values near the brachiocephalic and carotid ostia, possibly reducing the risk of endothelial dysfunction in the aortic root and the temporary lodging of microthrombi at the upper body arterial bifurcations before leaving as larger thrombus, no single configuration globally minimizes WSS on the arterial walls.…”
Section: Discussionmentioning
confidence: 83%
“…The general flow features of WSS distributions and flow patterns in the ascending aorta and aortic arch are in agreement with the result of Inci and colleagues. 11 In the present work, more emphasis was put on the aortic root region, especially the root WSS and pressure given various anastomosis configurations. The study demonstrated the significant influence of the type of anastomosis design on the aortic root flow.…”
Section: Discussionmentioning
confidence: 99%
“…Although the nonopening aortic valve is believed to be the main culprit for this complication, this observation indicates that maintaining a physiologic hemodynamic flow in the aortic root after the introduction of an LVAD may delay development of AVI. A few studies published recently have evaluated the effects of both LVAD-ascending aorta anastomosis configurations, along with their long-term impact on the aortic valve, [7][8][9][10][11][12] and cerebral embolization, 13 using computational fluid dynamics (CFD).…”
Section: See Editorial Commentary Page 704mentioning
confidence: 99%
“…Furthermore, our TAWSS results in ascending aorta for configurations 3 and 4 are in agreement with the study of Inci and Sorgüven considering azimuthal angle of 90° and inclination angles 15°–30°.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the shear stress, the anastomosis variation in angle or in location affects the distribution of wall shear stress, especially on aortic walls opposite to the outflow cannula connection (17), so these areas can be must be extensively studied because WSS is correlated with the development of atherosclerosis (38). As in the study of Inci and Sorgüven (14), our TAWSS's values in VAD cannula were higher than TAWSS in aorta due to the small diameter of the conduct in respect to the caliber of blood vessel.…”
Section: Discussionmentioning
confidence: 99%